2018
DOI: 10.1016/j.jelectrocard.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ECG algorithms designed to improve detect of transient myocardial ischemia to minimize false alarms in patients with suspected acute coronary syndrome

Abstract: Sensitivity was highly variable, due to the ST threshold selected, with the 100μV measurement point being superior to the 200μV amplitude threshold. Of all the algorithms tested, there was moderate sensitivity and specificity (70% and 68%) using the 100μV ST-segment threshold, integrated ST-segment changes in contiguous leads during a 5-min average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These studies showed that transient ischemic episodes are predictive for early, as well as long-term adverse cardiac events [ 24 , 25 , 26 ]. Sensitivity of automated ST-monitoring was shown to vary dependent on the chosen threshold for significant ST-shifts [ 35 ]. However, automated continuous ST-monitoring may identify patients with transient myocardial ischemia, who would have been missed due to under-sampling or human interpretation [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that transient ischemic episodes are predictive for early, as well as long-term adverse cardiac events [ 24 , 25 , 26 ]. Sensitivity of automated ST-monitoring was shown to vary dependent on the chosen threshold for significant ST-shifts [ 35 ]. However, automated continuous ST-monitoring may identify patients with transient myocardial ischemia, who would have been missed due to under-sampling or human interpretation [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, accurate classification of significant ST change at short-duration level can serve as groundwork to multiple succeeding goals. It’s been found that many false ST alarms in current in-hospital ECG monitors are induced by brief ST changes from turning, breathing, signal noise etc., and introducing a delay in monitoring algorithms can effectively reduce the number of alarms and mitigate alarm fatigue [3,20, 21]. Thus, the precise detection of short-duration ST change together with simple postprocessing steps, such as adding a delay, could provide great power in tackling the issue of excessive false positive alarms that plague the current ST monitoring software.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the present study is that the ST detection algorithm is built upon single-lead level, given that the database consists of ECG recordings with 2-or 3-lead configuration and annotation information is available at single-lead level. It has been found that true transient myocardial ischemia events typically have presence in contiguous leads (leads closed placed), and taking such information into account could improve detecting sensitivity [21]. Furthermore, some ischemic ST events are lead specific and can be only detectable through certain leads [22], so they might be missed by algorithms monitoring single or very few number of leads alone.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Pelter et al (2016) reported that transient myocardial ischemic events predicted worsening outcomes and actually proceeded symptoms by almost 3 h, suggesting continuous ECG may be able to more accurately capture the occlusive/non-occlusive nature of NSTEMI (Pelter et al 2016). Newer computerized algorithms may be superior in identifying transient ischemia which may prompt a transition toward use in hospital settings (Pelter et al 2018. While the hypothesis of spontaneous reperfusion is feasible for the continuum of arterial occlusion (Faramand et al 2021), it is more likely to affect NSTEMI with a sub-occluded artery (TIMI flow 2-3).…”
Section: Transient Occlusionmentioning
confidence: 99%